2008
DOI: 10.1007/s00125-008-0948-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between age at menarche and risk of diabetes in adults: results from the EPIC-Norfolk cohort study

Abstract: Aims/hypothesis Earlier age at menarche is associated with increased BMI and obesity risk from early childhood through to adulthood. We hypothesised that earlier age at menarche would also predict subsequent diabetes risk. Methods This was a population-based prospective cohort study of 13,308 women, who were aged 40 to 75 years between 1993 and 1997 and participating in the Norfolk cohort of the European Prospective Investigation into Cancer and Nutrition (EPIC-Norfolk). We used data on age at menarche and asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
133
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(154 citation statements)
references
References 33 publications
(39 reference statements)
12
133
1
6
Order By: Relevance
“…To the best of the authors’ knowledge, this is the first study to report on the association between age at menarche in patients with type 2 diabetes. It is reported that earlier‐onset menarche is associated with obesity and the development of type 2 diabetes mellitus in later life2, 3, 4, 5, 6, 7, 8, 9, 10, 11. The present results extend the association between age at menarche and obesity to patients with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…To the best of the authors’ knowledge, this is the first study to report on the association between age at menarche in patients with type 2 diabetes. It is reported that earlier‐onset menarche is associated with obesity and the development of type 2 diabetes mellitus in later life2, 3, 4, 5, 6, 7, 8, 9, 10, 11. The present results extend the association between age at menarche and obesity to patients with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 83%
“…Earlier age at menarche is associated with the future development of type 2 diabetes in Western and Asian populations4, 6, 7, 8, 9, 10, 11, and was associated with elevated HbA 1c , secondary to high BMI in the current study. These associations can be largely explained by increased adiposity.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…showing that earlier age of menarche onset increases the risk of adult diabetes and this appears to be M a n u s c r i p t mediated by greater adult adiposity (Lakshman et al, 2008). These data support the advice that healthy lifestyle with adequate caloric intake and physical activity should be strongly advocated in childhood.…”
Section: Earlier Age Of Menarche Onset and The Risk Of Obesity In Adusupporting
confidence: 69%